Analyzing Hospital Technology and Administrative Innovation's Effect on Performance: An Econometric Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hospitals worldwide are under pressure to improve patient happiness, organizational resilience, clinical quality, operational efficiency, and financial sustainability. Administrative innovation and hospital technology are important to transforming healthcare delivery. Hospital technology includes electronic health records, clinical decision support systems, automated provider order entry, telemedicine, HIE, diagnostic technologies, digital monitoring systems, and analytics-based management platforms. Administrative innovations include new managerial procedures, governance frameworks, workflow redesigns, quality management methods, strategic planning systems, human resource innovations, and data-driven decision-making. Despite the widespread promotion of administrative and technological innovation as performance-enhancing tools, empirical findings are inconsistent because hospital performance is multifaceted and innovation outcomes depend on implementation quality, organizational readiness, complementary capabilities, and time-lagged effects. This review examines theoretical, empirical, and econometric research on hospital technology, administrative innovation, and performance. Using panel data, fixed effects, dynamic models, regression analysis, and structural equation modeling, the study synthesizes health IT, organizational innovation, hospital productivity, and econometric research findings. Healthcare technology can improve process quality, information accessibility, care coordination, and efficiency, but its influence on financial results and cost reduction is not immediate, according to studies. Administrative innovation boosts technological value by improving coordination, accountability, leadership, workforce adaptation, and strategic alignment. Econometric research shows that administrative creativity and technology operate best together as complementary talents rather than separately. The article concludes that hospital performance evaluation must be longitudinal, multi-dimensional, and context-sensitive and recommends an integrated econometric framework for empirical research.